The COLO‐COHORT (Colorectal Cancer Cohort) study: Protocol for a multi‐centre, observational research study and development of a consent‐for‐contact research platform. (3rd June 2022) - Hampton, James S.; Koo, Sara; Dobson, Christina; Stewart, Christopher J.; Neilson, Laura J.; Montague, Kyle; Mitra, Suparna; Whelpton, John; Addison, Caroline; Kelly, Phil; Rushton, Stephen; Hull, Mark A.; et al.
Abstract: Aim: The COLO‐COHORT study aims to produce a multi‐factorial risk prediction model for colorectal neoplasia that can be used to target colonoscopy to those at greatest risk of colorectal neoplasia, ensuring that people are not investigated unnecessarily and maximizing the use of limited endoscopy resources. The study will also explore the link between neoplasia and the human gut microbiome. Additionally, the study aims to generate a cohort of colonoscopy patients who are 'research ready' through the development of a consent‐for‐contact (C4C) platform, to facilitate a range of colorectal cancer prevention studies to be conducted at scale and speed. Methods and analysis: This is a multi‐centre observational study involving sites across the UK. Recruitment is over a 6‐year period (2019–2025). Patients recruited to the study are those attending for colonoscopy. Patients are recruited into two groups, namely observational group A (10 000 patients) and C4C group B (10 000 patients), known as COLO‐SPEED (Colorectal Cancer Screening Prevention Endoscopy and Early Diagnosis; https://colospeed.uk ). Patients complete a health questionnaire, provide anthropometric measurements and submit biosamples (blood and stool—depending on the part of the study they are recruited into). Patients' colonoscopy and histology findings are also recorded. Models of factors associated with the presence of neoplasia at colonoscopy will be developed using logistic or multinomial regression. For internal validation, model discrimination and calibration will be assessed and bootstrapping and cross‐validation approaches used. To enable long‐term follow‐up for outcomes related to colorectal cancer and polyps, patients are asked to consent to follow‐up through data linkage with national databases. Dissemination: In keeping with good research practice, following analysis by the study team the study investigators will make the anonymized dataset available to other researchers. The C4C platform will also be accessible to other researchers. The study findings will be submitted for publication in peer‐reviewed journals and lay summaries will be disseminated to participants and the wider public.